Anthropometric measures are satisfactory substitutes for the DXA‐derived visceral adipose tissue in the association with cardiometabolic risk—The Tromsø Study 2015–2016 - Lundblad, Marie Wasmuth; Jacobsen, Bjarne Koster; Johansson, Jonas; Grimsgaard, Sameline; Andersen, Lene Frost; Hopstock, Laila Arnesdatter (Obesity Science & Practice, 2021)
Background - Body mass index (BMI) increases while cardiometabolic risk factors decrease in individuals in high-income countries. This paradoxical observation raises the question of whether current measures of overweight and obesity properly identify cardiometabolic risk. Methods - A total of 3675 participants (59% women) aged 40–84 years with whole-body dual-energy x-ray absorptiometry scans from the seventh survey of the Tromsø Study were included to examine the association between visceral adipose tissue (VAT) in grams and BMI, waist circumference (WC), waist-to-hip ratio (WHR), and waist-to-height ratio (WHtR). Further, their association with single cardiometabolic risk factors (blood pressure, triglycerides, total cholesterol, high-density lipoprotein [HDL] cholesterol, glycated hemoglobin, high-sensitivity C-reactive protein), modified single components from the ATP Ⅲ criteria for metabolic syndrome (hypertension, diabetes, high triglycerides, and low HDL cholesterol), and metabolic syndrome were examined. Results - VAT mass was strongly correlated with BMI (r ≥ 0.77), WC (r ≥ 0.80), WHR (r ≥ 0.58), and WHtR (r ≥ 0.78). WC was the strongest predictor for VAT (area under the curve: 0.90). Compared to anthropometric measures, the associations between VAT and metabolic syndrome as well as single components of metabolic syndrome were statistically significantly stronger, but the clinical differences were likely minor. Conclusion - Although VAT mass showed statistically stronger associations with cardiometabolic risk compared to traditional anthropometrics, the clinical importance was likely small. Simple, clinically available tools seem to satisfactory substitute for VAT to identify cardiometabolic risk.